2013
DOI: 10.1016/j.neubiorev.2012.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Atypical attentional networks and the emergence of autism

Abstract: The sociocommunicative impairments that define autism spectrum disorder (ASD) are not present at birth but emerge gradually over the first two years of life. In typical development, basic attentional processes may provide a critical foundation for sociocommunicative abilities. Therefore early attentional dysfunction in ASD may result in atypical development of social communication. Prior research has demonstrated that persons with ASD exhibit early and lifelong impairments in attention. The primary aim of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
277
2
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 341 publications
(310 citation statements)
references
References 290 publications
15
277
2
3
Order By: Relevance
“…3) seems to be a promising way to tackle a range of neurodevelopmental and drugrelated disorders. In ASD, early motor cognition anomalies resulting in basic motor-understanding difficulties could be one of the crucial neurocognitive markers for ASD detection (Becchio, Pierno, Mari, Lusher, & Castiello, 2007;Cattaneo et al, 2007;Fabbri-Destro et al, 2009;Parma, Bulgheroni, Tirindelli, & Castiello, 2013;Rochat et al, 2013), and potentially they could be tested even in infancy, before the onset of unequivocal behavioral symptoms (for reviews from nonmotor perspectives, see Jones, Gliga, Bedford, Charman, & Johnson, 2014;Keehn, Müller, & Townsend, 2013;Klin, Shultz, & Jones, 2015). Furthermore, considering that ASD is a lifelong condition that usually requires permanent assistance, motor cognition anomalies may assume a pivotal role for setting (early) rehabilitative protocols to improve social functioning (Pineda, Carrasco, Datko, Pillen, & Schalles, 2014;Rogers et al, 2014;Zwaigenbaum, Bryson, & Garon, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…3) seems to be a promising way to tackle a range of neurodevelopmental and drugrelated disorders. In ASD, early motor cognition anomalies resulting in basic motor-understanding difficulties could be one of the crucial neurocognitive markers for ASD detection (Becchio, Pierno, Mari, Lusher, & Castiello, 2007;Cattaneo et al, 2007;Fabbri-Destro et al, 2009;Parma, Bulgheroni, Tirindelli, & Castiello, 2013;Rochat et al, 2013), and potentially they could be tested even in infancy, before the onset of unequivocal behavioral symptoms (for reviews from nonmotor perspectives, see Jones, Gliga, Bedford, Charman, & Johnson, 2014;Keehn, Müller, & Townsend, 2013;Klin, Shultz, & Jones, 2015). Furthermore, considering that ASD is a lifelong condition that usually requires permanent assistance, motor cognition anomalies may assume a pivotal role for setting (early) rehabilitative protocols to improve social functioning (Pineda, Carrasco, Datko, Pillen, & Schalles, 2014;Rogers et al, 2014;Zwaigenbaum, Bryson, & Garon, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Autistic individuals show impairments in attentional networks, including the alerting, orienting and executive control networks [106]. Some researchers have suggested that the superior performance of autistic individuals in visual search is related to their atypical attention system.…”
Section: Visual Scene Analysis In Autismmentioning
confidence: 99%
“…In everyday environments, we balance investment of top-down controlled attention to achieve goal-directed behaviors with bottom-up monitoring for unexpected, but potentially relevant, environmental events [Keehn, M€ uller, & Townsend, 2013;Pashler, Johnston, & Ruthruff, 2001]. The tradeoff in attention between the amount of resources attributed to the current task goal versus those devoted to monitoring the environment for task-irrelevant, but important information is termed the "stability-flexibility dilemma" [Liljenstr€ om, 2003].…”
Section: Introductionmentioning
confidence: 99%
“…The tradeoff in attention between the amount of resources attributed to the current task goal versus those devoted to monitoring the environment for task-irrelevant, but important information is termed the "stability-flexibility dilemma" [Liljenstr€ om, 2003]. In people with ASD, resolution of this attentional dilemma may require consideration of sensory reactivity [Allen & Courchesne, 2001;Keehn et al, 2013;Liss et al, 2006]. Over-focused attentional styles have been related to over-reactivity and under-reactivity in people with ASD [Liss et al, 2006], while behavioral paradigms associate atypical arousal with difficulties disengaging attention [Keehn et al, 2013].…”
Section: Introductionmentioning
confidence: 99%